Three things scientists don't know about women farmers and climate change but really should - Puskur, Ranjitha; Deering, Karl (DownToEarth, 2022)
Just how well agriculture and food systems can cope with rising temperatures, floods and other climate shocks and stresses will be determined first and foremost by how much both women and men farmers can adapt to climate change. Farmers need to be supported to continue building resilient food systems that can nourish and sustain lives despite rising challenges, which have been compounded by setbacks such as the COVID-19 pandemic and the war in Ukraine. However, researchers do not currently know if existing solutions to climate change really do work for women or if they have only been designed primarily with men and their context in mind.